The Impact of Physics Modules Based on Problem Based Learning on The Problem-Solving Abilities of Students in the Material of Optical Instruments - Erika, Erika; Syahrial, Syahrial; Hikmawati, Hikmawati (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
The purpose of this study is to ascertain how students' problem-solving skills are affected by the use of a problem-based learning physics module. A nonequivalent control group design and a quasi-experimental research methodology are used. Test instruments in the form of descriptive questions and non-test instruments in the form of a questionnaire on student replies make up the instruments utilized. Students in grade XI at SMA Darul Falah for the academic year 2022–2023 make up the study population. Purposive sampling was used to choose the research sample, resulting in the experimental group consisting of 21 students from class XI MIPA 2 and the control group consisting of 21 students from class XI MIPA 1. For the experimental group, a customized problem-based learning module in physics was employed. The Problem-Solving Ability instrument consists of descriptive questions that have been tested for validity, reliability, difficulty level, and item discrimination. The experimental group's average post-test score was 83.66, compared to 60.09 for the control group. Both groups' data were uniformly distributed and homogeneous. The hypothesis test results indicated that the calculated t-value was greater than the critical t-value, specifically 6.33, which is higher than 2.02 for the post-test data. Therefore, the alternative hypothesis ( ) is accepted, and the null hypothesis ( ) is rejected, indicating an influence of using the physics module based on problem-based learning on students' problem-solving abilities in the topic of optical instruments. Based on the analysis of the questionnaire responses, students' responses improved after the implementation of the physics module based on problem-based learning, with an implementation percentage of 72%. In conclusion, there is an influence of using the physics module based on problem-based learning on students' problem-solving abilities in the topic of optical instruments.